Diagnostic efficacy of fecal markers combined with alarm symptoms in distinguishing functional and organic abdominal pain in children - Liu, Junhong; Wu, Bin; Ma, Bihong; Zhang, Xiaoyan (Frontiers in Pediatrics, 2026)
ObjectiveThis study assessed the diagnostic potential of fecal markers, calprotectin (FC), and occult blood (OB), in conjunction with alarm symptoms and blood markers, to differentiate functional abdominal pain (FAP) from organic disease in children.MethodsWe conducted a retrospective review of children with chronic abdominal pain who presented between April 2017 and April 2020, which included 347 classified as FAP and 224 classified as organic disease. Children with constipation in the functional group were included, and a slight elevation in FC in that group was considered non-inflammatory. FC interpretation included age/sex norms as opposed to percentiles, utilizing the cutoff of 60 µg/g, with justification given by the European Society for Paediatric Gastroenterology, Hepatology and Nutrition diagnostic criteria (Journal of Pediatric Gastroenterology and Nutrition, 2021; 72: 617–640). We also analyzed a second threshold of 100 µg/g. Families were sent instructions on how to do the OB test to reduce the false-positive rate. We utilized receiver operating characteristic curves to quantify diagnostic performance.ResultsThe organic disease had significantly greater alarm symptoms and abnormal fecal and blood indices compared with FAP (P < 0.05). Alarm symptoms with fecal markers produced diagnostic accuracy compared with the six strategies we tested (AUC = 0.841, sensitivity = 90.6%, specificity = 70.3%). Both of these scores exceeded either of the markers individually.ConclusionThe combination of alarm symptoms with fecal FC and OB tests provides a sensitive and specific non-invasive strategy for the differentiation of organic from FAP in children. The mild elevation of FC is likely indicative of functional constipation rather than inflammation, and attention should be given to diet and substances that affect OB outcome, specifically in children.